Topografía y cartografía arqueológica aplicada a reconstrucciones históricas en el Emirato de Sharjah (U.A.E.) - Farjas Abadía, M.; Fernández Pareja, T.; García Lázaro, F. J.; Llanos Viña, A. (ISIMU, 2016)
Isimu